Factors Influencing Seaweed Supply in Lakudo District, Central Buton Regency - Suhardin, Suhardin; Azhar Bafadal; Rosmawaty, Rosmawaty (International Journal of Technology and Education Research, 2023)
Lakudo District is one of the largest seaweed producing areas in Central Buton District. Based on data from the Fisheries Service of Central Buton Regency (2019) Lakudo District together with East Mawasangka have 1038.63 hectares of effective seaweed land area with a percentage of 38% in Central Buton Regency.This study aims to analyze the factors that influence seaweed supply in Lakudo District, Central Buton Regency. The location selection was carried out purposively with the consideration that this area is one of the central areas for seaweed production in Lakudo District, Central Buton Regency. This research was conducted from September to December 2022 in Lakudo District, Central Buton Regency, Southeast Sulawesi with 61 seaweed farmer respondents. The data analysis used is multiple linear regression analysis. The results showed that the variables that affect the supply of seaweed are the price of seaweed, production costs, number of workers and land area. An increase of IDR 1 in production costs will increase the supply of seaweed by 0 Kg. An increase of 1 worker will increase the supply of seaweed by 13.871 Kg. An increase of 1 Ha of land area will increase the supply of seaweed by 585.838 Kg. Keywords: Supply, Farmers, Seaweed.